A Comparative and Integrative Approach Identifies ATPase Family, AAA Domain Containing 2 as a Likely Driver of Cell Proliferation in Lung Adenocarcinoma - Robert Fouret; Julien Laffaire; Paul Hofman; Michèle Beau‐Faller; Julien Mazières; Pierre Validire; Philippe Girard; Sophie Camilleri‐Bröet; F. Vaylet; François Leroy-Ladurie; Jean‐Charles Soria; Pierre Fouret (2012)
To identify genetic changes that could drive cancer pathogenesis in never and ever smokers with lung adenocarcinoma.We analyzed the copy number and gene expression profiles of lung adenocarcinomas in 165 patients and related the alterations to smoking status. Having found differences in the tumor profiles, we integrated copy number and gene expression data from 80 paired samples.Amplifications at 8q24.12 overlapping MYC and ATAD2 were more frequent in ever smokers. Unsupervised analysis of gene expression revealed two groups: in the group with mainly never smokers, the tumors expressed genes common to normal lung; in the group with more ever smokers, the tumors expressed "proliferative" and "invasive" gene clusters. Integration of copy number and gene expression data identified one module enriched in mitotic genes and MYC targets. Its main associated modulator was ATAD2, a cofactor of MYC. A strong dose-response relationship between ATAD2 and proliferation-related gene expression was noted in both never and ever smokers, which was verified in two independent cohorts. Both ATAD2 and MYC expression correlated with 8q24.12 amplification and were higher in ever smokers. However, only ATAD2, and not MYC, overexpression explained the behavior of proliferation-related genes and predicted a worse prognosis independently of disease stage in a large validation cohort.The likely driving force behind MYC contribution to uncontrolled cell proliferation in lung adenocarcinoma is ATAD2. Deregulation of ATAD2 is mainly related to gene amplification and is more frequent in ever smokers.